AN IMPLEMENTATION OF ENCRYPTION AND DECRYPTION FOR SECURING DOCUMENT DATA USING A COMBINATION ADVANCED ENCRYPTION STANDARD AND RIVEST CODE-4 METHODS - Qadri Frans Husein; Mhd Furqan; Yusuf Ramadhan Nasution (INFOKUM, 2022)
An Confidentiality of data is of greater concern to all of us, to ensure that stored information cannot be read, opened or even accessed by unauthorized parties, it is necessary to secure and protect the integrity of the documents sent. So to minimize these actions, a system is needed to provide protection and security so that it is difficult to solve by irresponsible people. Some methods that can be used to do this are AES-128 and RC4, a combination of which creates a high level of data security. Based on testing AES-128 and RC4 are able to increase the level of data security in the form of documents by way of encryption and still maintain the original documents when the results of the decryption process.